Characteristic overview of aplastic anemia at Sanglah Hospital, Bali-Indonesia in 2017-2018 - Komang Agus Widhy Utama Putra; A.A Ngurah Subawa; A.A Wiradewi Lestari (Intisari Sains Medis, 2019)
Background: Aplastic anemia is a rare disease of anemia which characterized by pancytopenia due to spinal cord hypoplasia. This can occur in people of any age, race, and gender with different degree of severity, with incidence rate is two until three times higher in Asia than the West. This study aims to determine the characteristic of aplastic anemia based on age, gender, laboratory examination, and severity in Sanglah Hospital.Methods: This research is a cross sectional descriptive study with sources of data were medical records of aplastic anemia patients at Sanglah Hospital in the last 2 years, 2017-2018. Distribution of research variables is gender, age, laboratory examination, and severity.Results:The result showed that 11 data were 6 (55%) male and 5 female (45%), with the mean age was 48 ± 14 years. The highest incidence occurred in the age range of 26-60 years old with 7 patients (64%). In this study the average hemoglobin level obtained was 9.94 ± 1.46 g/dL with range between 6.65 to 12.49 g/dL. The average number of leukocytes was 11.91 ± 24.52 x 109 L with range of leukocytes is 1.99-84.58 x 109/L. The average number of absolute Neutrophils and percent was 1.53 ± 1.52 x 109/L and 25.99 ± 25.79% with range between 0.06 – 4.53 x 109/L and 2.3 - 70.83%. The average platelet count was 24.77 ± 11.35 x 109/L with range between 4.25 – 42.58 x 109/L. The highest cases were nonsevere aplastic anemia (NSAA) with 7 people (64%).Conclusion: The value of laboratory parameters for complete blood examination (leukocytes, platelets, hemoglobin, and neutrophils) in patients with aplastic anemia at Sanglah General Hospital is still very low, so it is a challenge for clinicians to carry out treatment of aplastic anemia and management related complications.